Pelatihan Pembuatan Abon dan Label Kemasan Produk Olahan Ikan Mas di RW. 07 Desa Ciasihan - Erneza Dewi Krishnasari; Yaddarabullah Yaddarabullah (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
Ciasihan Village is one of the villages in Pamijahan Sub-District, Bogor Regency. Most of the land is paddy field so that many residents work as farmers. But besides farming, the residents also have ponds for the cultivation of tilapia and carp. At the time of fish harvest, residents sell the fish without being processed so the selling price tends to be low. To increase their income, an effort is needed to increase the added value of the fish by processing it into fish floss. To sell the product, it must be packaged well so it is easy to recognize and use. Based on this background, the empowerment given to the villagers of Ciasihan includes training on making the fish floss and making packaging labels. The purpose of this empowerment is not only to make food more durable, but also to provide a visual identity for the processed food products of Ciasihan Village.